Urgensi Pengaturan Syarat Insolvensi Dalam Undang-Undang Kepailitan dan Penundaan Kewajiban Pembayaran Utang - Surjanto, Diana (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 3 No 2 (2018), 2018)
The Law Number 37 in 2004 regarding Bankruptcy and Suspension of Debt Payment Obligations (The Law Number 37 in 2004) did not regulate insolvency requirement in determining the bankruptcy of debtors. Not surprisingly, bankruptcy decisions against debtors imposed by the Indonesian Commercial Court under the law were very disappointing for the business and investment in Indonesia, because debtors can be terminated without seeing their ability to settle debts. This was on the contrary to the universal philosophy of bankruptcy law, that only debtors who are already in an insolvency state can be declared bankrupt by the court after being requested to bankrupt the intended debtor. The purpose of this research was to know and analyze the relationship between bankruptcy and insolvency and also the regulation of insolvency terms in UUK-PKPU. The type of the research was normative law research, with the statute, conceptual, and comparative approach. The sources of legal materials used in this research were primary and secondary legal materials. The analysis technique of legal materials used analytical descriptive techniques. The result of the research obtained that bankruptcy and insolvencyhave a very close relationship where a person or legal entity should be declared bankrupt if the person or legal entity was insolvent. Urgency for the government to revise The Law Number 37 in 2004 that did not regulate insolvency requirement in determining the bankruptcy of debtors, so that justice, expediency, and legal certainty were created.